Influence of Strategic Leadership on the Performance of Hospitality Companies in Maputo Province, Mozambique - Boane, Celia Antonio; Gichunge, Evangeline; Miluwi, Joshua (International Journal of Professional Practice, 2024)
The drivers of strategy implementation are crucial for achieving strategic goals. The study aims to identify critical elements that contribute to enhanced performance in the Hotel industry. It examines the influence of strategic leadership on the performance of hospitality companies in Maputo Province, Mozambique, focusing on key elements that enhance hotel performance. The study, grounded in Strategic Leadership theory, utilized a descriptive survey research design. Data were collected from 10 hotels, with participants including 10 Chief Executive Officers, 10 relationship managers, 10 operations managers, 10 IT managers, and 10 strategic leaders. A total of 50 respondents were selected through simple random sampling method, and they responded to both limited-choice and open-ended questions. To ensure the validity of the research, a pre-test was conducted at Vip Grand Hotel Maputo, with one relationship manager and two IT staff. The findings were illustrated using descriptive statistics, frequency charts, and detailed explanations, while inferential statistics were analyzed through multiple regression and correlation analysis. Results indicated that strategic leadership significantly influences the performance of hospitality companies. A correlation coefficient of 0.089 was found between strategic leadership and performance, with statistical significance at a p-value of 0.05. Participants highlighted the importance of effective leadership, emphasizing that senior management must cultivate behaviors and practices that drive performance. The study concluded that effective leadership is essential for achieving customer satisfaction, profitability, market share, operational efficiency, informed decision-making, and resource management. As a result, the study recommends that hotel CEOs prioritize a culture of creativity and innovation. This can be accomplished by encouraging employees to share ideas, experiment with new approaches, and continuously improve processes, thereby enhancing overall hotel performance.